Shear Modulus of Elasticity for Thin-Walled Trapezoidal Corrugated Cores of Seven-Layer Sandwich Plates - LEWIŃSKI, Jerzy; MAGNUCKA-BLANDZI, Ewa; SZYC, Wacław (Engineering Transactions, 2015)
The subject of the paper are two thin-walled trapezoidal corrugated cores of seven-layer sandwich plates. Transverse shear modules of these cores are analytically determined and numerically - FEM studied. Results of both methods are compared for an example plate.